2014
DOI: 10.2471/blt.14.138560
|View full text |Cite
|
Sign up to set email alerts
|

Implementing rapid testing for tuberculosis in Mozambique

Abstract: ProblemIn Mozambique, pulmonary tuberculosis is primarily diagnosed with sputum smear microscopy. However this method has low sensitivity, especially in people infected with human immunodeficiency virus (HIV). Patients are seldom tested for drug-resistant tuberculosis.ApproachThe national tuberculosis programme and Health Alliance International introduced rapid testing of smear-negative sputum samples. Samples were tested using a polymerase-chain-reaction-based assay that detects Mycobacterium tuberculosis deo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 6 publications
2
41
0
Order By: Relevance
“…And even worse, 53% of those with Rifampicin resistance did not start treatment. 28 Raising the question whether it is ethical to expand only diagnostic services when the health system is not able to cope with the extra cases. 29 Nevertheless, for rural settings, with structural difficulties for standard GeneXpert installation, same-day sputum microscopy approach could be an alternative as it has demonstrated to have the same diagnostic accuracy as the traditional 2 days sampling and has also been endorsed by WHO.…”
Section: Discussionmentioning
confidence: 99%
“…And even worse, 53% of those with Rifampicin resistance did not start treatment. 28 Raising the question whether it is ethical to expand only diagnostic services when the health system is not able to cope with the extra cases. 29 Nevertheless, for rural settings, with structural difficulties for standard GeneXpert installation, same-day sputum microscopy approach could be an alternative as it has demonstrated to have the same diagnostic accuracy as the traditional 2 days sampling and has also been endorsed by WHO.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most diagnostic tests are evaluated primarily in well-funded trials and demonstration studies, without good evidence of how they perform in the real world. For example, Xpert MTB/RIF was recommended on the basis of high-quality data about its accuracy and cost-effectiveness under controlled conditions and in a large field trial 26 ; however, emerging evidence has suggested that, in many settings, the characteristics of Xpert may be different when implemented in the field -including its sensitivity 69 , calibration 70 , positive predictive value (owing to low pre-test probability) 71 , and accuracy for rifampin resistance 72 . To make accurate assessments of the incremental value of diagnostics, we should collect such data early after launch, and update expectations and recommendations as those data become available.…”
Section: S65mentioning
confidence: 99%
“…Moreover, for TB diagnosis, the Xpert MTD/RIF assay is a fully automated nucleic acid ampli cation testing (NAAT) that can deliver a result in about 2 h, Which was widely thought to be e cient and cost-effective [13] . It has been endorsed by the World Health Organization and widely deployed [17]- [22] . Nevertheless, as yet, for most pathogens, especially the pathogens mainly caused cerebral parenchymal lesions, had low sensitivity and speci city means of diagnosis.…”
Section: Discussionmentioning
confidence: 99%